Implementasi Kebijakan Penanganan Tindak Kekerasan Perempuan Di Dinas Pemberdayaan Perempuan Dan Perlindungan Anak Kota Palu - jannah, miftahul; Nasrullah; Rachmad (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
This study aims to determine how the implementation of policies for handling women's violence in the Office of Women's Empowerment and Child Protection in Palu City. The basis of this study uses the basis of qualitative research with a descriptive approach, while data collection techniques are carried out by observation, interviews, and documentation. The data used in this study is in the form of primary data and secondary data. The determination of informants in this study uses purposive by assigning 4 (people) informants. Data analysis in this study is data reduction, data presentation, and conclusions. The theory used in this study is the theory by Donald Van Metter and Carl Van Horn, There are 6 aspects that need to be considered, namely 1) standards, goals, and policy objectives, 2) resources, 3) characteristics of implementing organizations, 4) communication between implementing organizations, 5) implementing attitudes, and 6) economic, social, and political environment. Based on the results of the research obtained, it was concluded that the factors that caused the lack of optimal implementation of policies for handling acts of violence against women were the lack of information or socialization to the community regarding the prevention and handling of acts of violence, lack of budget in handling acts of violence against women, and the unavailability of UPTD to support the handling of acts of violence against women.